STUDENTS’ LEARNING ENGLISH EXPERIENCE IN ENGLISH LITERATURE STUDY PROGRAM AT KHAIRUN UNIVERSITY - Samad, Farid; Jusnita, Naniek; Aboe, Roswita M; Latif, Taib; Daud, Abdul Halim (Cakrawala Bahasa, 2025)
This research aims to explore students learning English experience in their learning practice both online and offline situation. It involved fifteen (15) students of fifth semester in English literature study program at Khairun University. This is qualitative descriptive method, and the data gathered from questionnaire and interview analysis. Based on result data analysis, students’ learning experience factors such interaction, instruction, instructor, management and technology had influenced their language acquisition, speaking communication, learning motivation, comfortable zone, and accessibility in learning class both online and offline situation. Those learning factors contributed to positive teaching and learning practice to enhance students’ opportunities for interaction and feedback, it is influenced their language learning strategies and preferences. The process of teaching and learning process does not always run well as smooth as the educator and students expected. However, students can extend their learning English experience and acquire more knowledge from learning factors.